German language as a source of lexical borrowings - Pryhodzich, Alena A. (Human in the Socio-Cultural Dimension, 2020)
The article analyzes the germanisms borrowed from the old Belarusian language during the 14th‒18th centuries both directly from the Germanic languages and through the mediation of primarily the Old Polish language. The author gives numerous examples of borrowings in relation to certain lexical-thematic groups; the first date of the fixation of such units in the monuments of writing is indicated. Based on the first results of the international project «Migrating words: ways of German loanwords from Polish to East Slavic languages» (project manager is professor of the Carl von Ossietzki University of Oldenburg), the quantitative parameters of such words are determined on the material of I. Nosovich’s dictionary, historical and explanatory dictionaries of the modern Belarusian language. The conclusion is drawn on the need for further study of the place and role of germanisms in the lexical composition of the Belarusian language, also in connection with the preparation of a multi-volume edition of a new explanatory dictionary of the modern Belarusian language.